2001
DOI: 10.1016/s1011-1344(01)00227-5
|View full text |Cite
|
Sign up to set email alerts
|

Retinal photodamage

Abstract: The retina represents a paradox, in that, while light and oxygen are essential for vision, these conditions also favour the formation of reactive oxygen species leading to photochemical damage to the retina. Such light damage seems to be multi-factorial and is dependent on the photoreactivity of a variety of chromophores (e.g., vitamin A metabolites, lipofuscin, melanin, flavins, porphyrins, carotenoids) endogenous to the retina. The aim of this article is to provide a detailed review of our current understand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
263
0
5

Year Published

2004
2004
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 331 publications
(282 citation statements)
references
References 141 publications
3
263
0
5
Order By: Relevance
“…Since rhodopsin is, by far, the dominant green-absorbing molecule in the albino rat retina and the action spectrum of retinal light damage corresponds to the absorption spectrum of rhodopsin (see Organisciak and Winkler, 1994, and references cited therein), the light-induced exacerbation of the SLOS rat retinal degeneration likely is rhodopsin-mediated. Hence, in agreement with current models implicating lipid peroxidation in the mechanism of retinal light damage (Wenzel et al, 2005;Glickman, 2002;Boulton et al, 2001;Organisciak and Winkler, 1994), we speculate that light absorption by rhodopsin triggers the formation of pro-oxidants, which cause oxidation of 7DHC to cytotoxic oxysterols. Since 7DHC is appreciably absent from normal retinas, this explains the hypersensitivity to retinal light damage observed in the SLOS rat model compared to normal albino rats.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Since rhodopsin is, by far, the dominant green-absorbing molecule in the albino rat retina and the action spectrum of retinal light damage corresponds to the absorption spectrum of rhodopsin (see Organisciak and Winkler, 1994, and references cited therein), the light-induced exacerbation of the SLOS rat retinal degeneration likely is rhodopsin-mediated. Hence, in agreement with current models implicating lipid peroxidation in the mechanism of retinal light damage (Wenzel et al, 2005;Glickman, 2002;Boulton et al, 2001;Organisciak and Winkler, 1994), we speculate that light absorption by rhodopsin triggers the formation of pro-oxidants, which cause oxidation of 7DHC to cytotoxic oxysterols. Since 7DHC is appreciably absent from normal retinas, this explains the hypersensitivity to retinal light damage observed in the SLOS rat model compared to normal albino rats.…”
Section: Discussionsupporting
confidence: 91%
“…6-week-old; hence, these findings are comparable to those previously observed in 4-week-old AY9944-treated rats (Fliesler et al, 1999), but are unlike those observed in 10-week-old AY9944-treated rats (Fliesler et al, 2004), where retinal degeneration was observed. As expected, photoreceptor loss from CE rat retinas was modest, with severe cellular damage and loss being relatively restricted geographically to the superior central region, in complete agreement with the prior findings of several other labs (see Wenzel et al, 2005;Glickman, 2002;Boulton et al, 2001;Organisciak and Winkler, 1994). Retinal histology in the inferior central zone and in the peripheral retina of both hemispheres appeared relatively normal.…”
Section: Histology and Quantitative Morphometrysupporting
confidence: 89%
See 2 more Smart Citations
“…These results show that inhibition of the chymotrypsin-like activity can critically affect cell survival under stressful conditions. Considering that the retina in vivo is particularly prone to oxidative stress due to the high oxygen tension and metabolic activity as well as the presence of photosensitive pigments that generate reactive oxygen species (Boulton et al, 2001), it is possible that this tissue periodically experiences sufficient stress to surpass a threshold for maintaining cellular redox homeostasis. Therefore, the loss in chymotrypsin-like activity in aged retina could result in reduced tolerance of oxidative stress via several mechanisms, including the decreased clearance of oxidatively damaged proteins.…”
Section: Consequences Of Proteasome Inhibitionmentioning
confidence: 99%